I hope we can handle it': A study examining student ability beliefs and motivations before transition. - Debbie Meharg; Stephanie Craighill; Alison Varey; Jenny Tizard (University of Aberdeen, School of Education, 2016)
This paper employs the 'Expectancy-Value Model of Achievement Motivation' (Wigfield and Eccles, 2000) to identify performance barriers and facilitators for further education students continuing their studies at university. Using this model to understand student ability beliefs and motivations prior to university study identifies potential performance challenges and informs strategies to improve the transition experience from further to higher education. Three focus groups of students planning to transition to university were asked to discuss a number of theoretical strands inherent to the Expectancy-Value Model, such as ability beliefs and motivation components, to determine student potential to perform and persist with higher education. Findings revealed students had decisive and clear motivations for transitioning to university however a number of barriers were perceived which shaped their ability beliefs and could potentially impact their performance. Outcomes of this study inform approaches to enhance the transition experience of students to higher education and are particularly relevant as the Scottish Government aims to remove barriers and widen participation. Additionally, the research findings make an important contribution to informing the approach of university and further education institution (FEI) staff, guiding policy makers and knowledge transfer.